2020
DOI: 10.1037/dev0000854
|View full text |Cite
|
Sign up to set email alerts
|

Chinese and South Korean children’s moral reasoning regarding the fairness of a gendered household labor distribution.

Abstract: This study explored age-related changes in Chinese and Korean children's fairness judgments and reasoning regarding the gendered division of household labor. The majority of previous research on this issue has focused on adults' experiences and has been conducted in Western countries. Interviews were conducted with 133 children, 65 Chinese and 68 South Korean, ages 9 -11 (N ϭ 48), 12-14 (N ϭ 43), and 16 -18 (N ϭ 42). Despite country differences in women's involvement in the workforce, in both countries women d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…When judging about helping in their own homes, participants were more likely to say that female household members should have been responsible for meal preparation more than male members. This finding is consistent with prior work around the acceptance of a family's gendered division of household work (Midgette, 2020a, 2020b). Gendered ideas about household work, when accepted by a new generation, may perpetuate gender inequalities in household contributions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When judging about helping in their own homes, participants were more likely to say that female household members should have been responsible for meal preparation more than male members. This finding is consistent with prior work around the acceptance of a family's gendered division of household work (Midgette, 2020a, 2020b). Gendered ideas about household work, when accepted by a new generation, may perpetuate gender inequalities in household contributions.…”
Section: Discussionsupporting
confidence: 90%
“…However, gender differences in their experienced responsibilities were far more pronounced. On average, participants indicated that mothers should have been less responsible than they were, and that fathers should have been more responsible (Midgette, 2020a). The ethnic and gender differences in these judgments uncover ways in which judgments about helping depend on one's experiential background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies may include other cultural samples to further explore this issue. Moreover, while pragmatic considerations have been noted by domain theorists as an important consideration in making decisions (Midgette, 2020; Smetana et al, 2014), and were found to justify many of the “other” transgressive events, we also found that many participants were also reporting transgression events that were purely concerned with their academic outcomes. This finding is in keeping with the fact that Chinese children and adolescents are strongly encouraged to focus on academics and spend the majority of their time studying (Chen et al, 2003; Ho, 1996; Li & Hein, 2019).…”
Section: Discussionmentioning
confidence: 47%
“…Finally, as shown in other studies (Behari et al., 2005; Hristova et al., 2009), female patients’ poor QoL may be a result of their more active participation in everyday household activities such as cooking, increasing concern for poor performance. There is substantial research showing that women do more housework than men in East Asian countries (Hu & Mu, 2021; Midgette, 2020; Oshio et al., 2012). Therefore, although our study did not assess the participation of female patients in housework, we still considered it as a possible reason why the QoL of female patients is lower than that of men.…”
Section: Discussionmentioning
confidence: 99%